ҚОРАҚАЛПОҚ ЛИРО-ЭПИК ДОСТОНЛАРИНИНГ ШАКЛЛАНИШ ЖАРАЁНИ МАСАЛАЛАРИ - Жаксимова, У.Ж. (SCIENCE and SOCIETY, 2022)
The article indicates that the Karakalpak lyric-epic epics, such as "Khurlika-Hamra", "Garib-Oshik", "Najepuglan", "Yusuf-Zilikha", "Sayatkhon-Hamra", are an integral part of our national cultural heritage, the complexity of the events, the diversity of the heroes, the difference of traditions are reflected in the beauty of the image style and the richness of the colors. There is no doubt that the epics reflect the way of life, culture, beautiful nature of our country, family relations, religion, customs and social events, which serve as a model for the present generation.